The immunomodulatory and antitumor properties of the bacterial metalloprotease Oligopeptidase A are mediated by TLR4/MyD88/TRIF and MAPK signaling pathways - Silva, Priscila; Silva, Gabrielli Novaes; Melo, Filipe Menegatti; de Amat Herbozo, Carolina; Sellani, Tarciso Almeida; Tomaz, Samanta Lopes; De Melo, Amanda Campelo L.; Da Silva, Larissa Reis; Berzaghi, Rodrigo; Marcondes, Marcelo F. M.; Bronze, Fellipe; Paschoalin, Thaysa; et al. (Frontiers in Immunology, 2025)
IntroductionImmunosuppressive factors within the tumor microenvironment hinder effective antitumor immune responses and limit the efficacy of current immunotherapies. Immunomodulators offer an alternative by activating immune effectors. Proteases from various sources used as cancer therapy adjuvants have shown promise in inhibiting tumor growth. Our previous work showed that the bacterial metalloprotease arazyme has a strong in vivo antimetastatic effect in the B16F10-Nex2 murine melanoma model. Interestingly, heat-inactivated arazyme also exhibited antitumor properties dependent on an intact adaptive immune response, highlighting its immunomodulatory role. To assess whether this effect is unique to arazyme, we examined another bacterial metalloprotease, Oligopeptidase A (OpdA).MethodsOpdA was produced and purified. Endotoxin levels were measured. C57BL/6 mice received intravenous B16F10-Nex2 cells, followed by treatments with either active or heat-inactivated OpdA. Pulmonary nodules were counted. Immune cells involved in the response were characterized using FACS and depletion experiments. Cytokines were measured by ELISA and intracellular cytokine analysis. OpdA receptor activation was studied in bone marrow-derived cells from knockout and wild-type mice using inhibitors.ResultsHeat-inactivated OpdA significantly reduced metastasis, dependent on tumor-specific CD4+ and CD8+ T cells and IFN-γ, both locally and systemically, with decreased IL-10 levels suggesting a proinflammatory environment. Treatment increased secretion of nitric oxide, IL-12p40, and TNF-α from bone marrow cells via enzymatic activity, involving MyD88/TRIF and MAPK pathways. Conclusion: OpdA shows potential as a tumor vaccine adjuvant, promoting antigen presentation and tumor-specific immune responses.